2007
DOI: 10.1097/wad.0b013e318065c481
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Diagnosis Disclosure

Abstract: This paper reports the findings of a descriptive, exploratory, qualitative study of patient and caregiver perspectives of the disclosure of a dementia diagnosis. Data were collected at 3 points in time: (1) the disclosure meeting, (2) patient and caregiver interviews, and (3) focus group interviews. Thirty patient-caregiver dyads participated in the disclosure meetings at the Geriatric Day Hospital at the Ottawa Hospital, Ottawa, Canada. Within a week of the disclosure of diagnosis, 27 (90%) patients and 29 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…The findings of this study would therefore parallel the findings of studies [37,38] that people with dementia are often unaware of their condition, pre-diagnosis.The news of a diagnosis of dementia was met with feelings of shock and disbelief and was upsetting for all three women. This study therefore supports previous findings [39][40][41] with regard to a diagnosis of dementia causing emotional distress.…”
Section: Discussionsupporting
confidence: 73%
“…The findings of this study would therefore parallel the findings of studies [37,38] that people with dementia are often unaware of their condition, pre-diagnosis.The news of a diagnosis of dementia was met with feelings of shock and disbelief and was upsetting for all three women. This study therefore supports previous findings [39][40][41] with regard to a diagnosis of dementia causing emotional distress.…”
Section: Discussionsupporting
confidence: 73%
“…It often took a trigger event or tipping point such as a hospitalisation or bereavement [34],[37],[40],[42],[51],[53],[92],[114],[118],[138] before people sought help. Family members often recognised something was wrong before the person with dementia did, and were frequently instrumental in obtaining a diagnosis [32],[40],[41],[45],[54],[72],[88],[115],[129]. There was evidence of greater stigma among minority ethnic populations and evidence that they were less likely to recognise symptoms of dementia as an illness than white individuals, and more likely to ascribe these symptoms to the ageing process [32],[86],[118],[119].…”
Section: Resultsmentioning
confidence: 99%
“…A desire to preserve a pre-dementia identity sometimes led to people being reluctant to disclose their diagnosis to family or wider social networks [52],[53],[109], which could lead to social isolation [53],[62],[105]. Despite this, some studies suggested that eventually both the individuals with dementia and their carers reached a state of acceptance [36],[45],[88],[91].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiences related to care coordination, physician-patient relationships, medical errors, use of prescription medications and access to needed care have been identified as common areas that lead to a global perception of dissatisfaction in general health system quality (Blendon et al ., 2003). Similar comparative concerns develop surrounding the acceptance of screening and disclosing a diagnosis of a disease or impairment such as dementia (Brodaty et al ., 1994; Byszewski et al ., 2007; Cahill et al ., 2006; Connell and Gallant, 1996; Domenighetti et al ., 2003). …”
Section: Introductionmentioning
confidence: 99%